Sex differences in brown adipose tissue activity and cold-induced thermogenesis - Herz, Carsten T.; Kulterer, Oana C.; Prager, Marlene; Marculescu, Rodrig; Langer, Felix B.; Prager, Gerhard; Kautzky-Willer, Alexandra; Haug, Alexander R.; Kiefer, Florian W. (Molecular and cellular endocrinology, 2021)
Brown adipose tissue (BAT) is suggested to exhibit a sexual dimorphism and thus contributes to the observed sex differences in cardiometabolic risk observed between women and men. Clinical data supporting this hypothesis are however scarce. The aim of this study was to investigate the relationship between BAT activity and sex using positron emission tomography (PET) – the current gold-standard for BAT quantification. In this study, we included 95 subjects with a wide BMI range (20–55 kg/m2) aged from 18 to 50 years. Avoiding shivering, participants were cooled with a water-perfused vest to achieve adequate BAT activation. BAT activity was determined by 18F-fluorodeoxyglucose PET/computed tomography (18F-FDG PET/CT). Cold-induced thermogenesis (CIT) was quantified by indirect calorimetry. BAT was present in 44.6% of pre-menopausal women and in 35.9% of men (p = 0.394). CIT was significantly higher in women (p = 0.024). Estradiol levels were positively associated with CIT independent of age, sex, body fat and other sex hormones (b = 0.360, p = 0.016). In women, CIT decreased during the menstrual cycle, with lower levels in the luteal phase similar to median concentrations in men. The prevalence of cold-activated BAT is slightly but non-significantly higher in pre-menopausal women than men. CIT is increased in females and independently associated with estradiol, suggesting that sex hormones may play a role in different thermogenic responses between men and women. •We found a non-significantly higher prevalence of active BAT in pre-menopausal women compared to men.•Cold-induced thermogenesis (CIT) was significantly increased in pre-menopausal women.•Among the sex hormones, only estradiol was positively associated with CIT.•Estradiol might contribute to a higher thermogenic response in pre-menopausal women compared to men.